Role of geometrical cues in bone marrow-derived mesenchymal stem cell survival, growth and osteogenic differentiation - Gupta, Dhanak; Grant, David M.; Zakir Hossain, Kazi M.; Ahmed, Ifty; Sottile, Virginie (SAGE, 2018)
Mesenchymal stem cells play a vital role in bone formation process by differentiating into osteoblasts, in a tissue that offers not a flat but a discontinuous three-dimensional (3D) topography in vivo. In order to understand how geometry may be affecting mesenchymal stem cells, this study explored the influence of 3D geometry on mesenchymal stem cell-fate by comparing cell growth, viability and osteogenic potential using monolayer (two-dimensional, 2D) with microsphere (3D) culture systems normalised to surface area. The results suggested lower cell viability and reduced cell growth in 3D. Alkaline phosphatase activity was higher in 3D; however, both collagen and mineral deposition appeared significantly lower in 3D, even after osteogenic supplementation. Also, there were signs of patchy mineralisation in 3D with or without osteogenic supplementation as early as day 7. These results suggest that the convex surfaces on microspheres and inter-particulate porosity may have led to variable cell morphology and fate within the 3D culture. This study provides deeper insights into geometrical regulation of mesenchymal stem cell responses applicable for bone tissue engineering.